Life cycle energy analysis of residential wooden buildings versus concrete and steel buildings: A review - Schenk, Daniela; Amiri, Ali (Frontiers in Built Environment, 2022)
Around 40% of global energy consumption can be attributed to the construction sector. Consequently, the development of the construction industry towards more sustainable solutions and technologies plays a crucial role in the future of our planet. Various tools and methods have been developed to assess the energy consumption of buildings, one of which is life cycle energy analysis (LCEA). LCEA requires the energy consumption at each stage of the life cycle of a product to be assessed, enabling the comparison of the impact of construction materials on energy consumption. Findings from LCEAs of buildings suggest that timber framed constructions show promising results with respect to energy consumption and sustainability. In this study a critical analysis of 100 case studies from the literature of LCEAs conducted for residential buildings is presented. Based on the studied material, the embodied, operational, and demolition energies for timber, concrete and steel buildings are compared and the importance of sustainable material selection for buildings is highlighted. The results reveal that on average, the embodied energy of timber buildings is 28 – 47% lower than for concrete and steel buildings respectively. The mean and median values of embodied emissions are 2,92 and 2,97 for timber, 4.08 and 3,95 for concrete, and 5,55 and 5,53 GJ/m2 for steel buildings. Moreover, the data suggests that the energy supply system of residential buildings plays a larger role in the operational energy consumption that the construction material. In addition, climate conditions, insulation detail, windows and building surfaces, and building direction are the other energy use role players. Finally, it was found that the demolition energy contributes only a small amount to the total life cycle energy consumption. This study demonstrates the significance of embodied energy when comparing the life cycle energy requirements of buildings and highlights the need for the development of a more standardized approach to LCEA case studies.